2019
DOI: 10.1093/jncics/pkz084
|View full text |Cite
|
Sign up to set email alerts
|

Race, Socioeconomic Status, and Health-Care Access Disparities in Ovarian Cancer Treatment and Mortality: Systematic Review and Meta-Analysis

Abstract: BackgroundOvarian cancer remains a leading cause of death from gynecological malignancies. Race, socioeconomic status (SES), and access to health care are important predictors of quality treatment and survival. We provide a systematic review and meta-analysis on the role of these predictors on disparities in ovarian cancer treatment and mortality.MethodsUsing the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines, we searched PubMed, EMBASE, and Scopus for relevant articles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 53 publications
1
75
0
Order By: Relevance
“…TTD differed significantly by race and ethnicity once other covariables were accounted for; this has been demonstrated in other cancers 35,36 and reflects the broader racial and ethnic disparities in ovarian cancer care in the United States. 1,[37][38][39][40][41] Increased TTD for Hispanic patients is likely the result of complex social determinants of health and elements of structural racism within the US Cancer November 15, 2021 medical system leading up to diagnosis. 42 These structural problems within the medical system are especially important to address in a disease such as ovarian cancer, where adherence to guideline recommendations can mitigate survival disparities between races.…”
Section: Resultsmentioning
confidence: 99%
“…TTD differed significantly by race and ethnicity once other covariables were accounted for; this has been demonstrated in other cancers 35,36 and reflects the broader racial and ethnic disparities in ovarian cancer care in the United States. 1,[37][38][39][40][41] Increased TTD for Hispanic patients is likely the result of complex social determinants of health and elements of structural racism within the US Cancer November 15, 2021 medical system leading up to diagnosis. 42 These structural problems within the medical system are especially important to address in a disease such as ovarian cancer, where adherence to guideline recommendations can mitigate survival disparities between races.…”
Section: Resultsmentioning
confidence: 99%
“…The burden is worsened in developing countries such as India, where nearly 70% of the national population resides in rural areas and must travel to urban tertiary care centers for treatment ( 101 , 102 ). Studies have also revealed racial disparities in access to cancer treatment worldwide ( 103 , 104 ). Furthermore, inequalities between SES groups are also significant within developing countries.…”
Section: Resultsmentioning
confidence: 99%
“…Black and Hispanic women, compared with White women, and women of lower SES were also less likely to receive radiation therapy after breast‐conservation surgery, as recommended in treatment guidelines 96 . Disparities in the receipt of treatment also exists for most other cancers, such as cancers of the colorectum, 97 pancreas, 98 uterus, 99 ovary, 100 and esophagus 101 . Increased use of precision medicine and other innovative, advanced medical technologies, which are generally associated with higher costs, may result in further widening of disparities in the receipt of guideline‐concordant cancer treatments 89,102,103,104,105,106 …”
Section: Factors That Contribute To Cancer Disparities Across the Can...mentioning
confidence: 99%